2021
DOI: 10.2196/24342
|View full text |Cite
|
Sign up to set email alerts
|

De-Implementing Opioid Use and Implementing Optimal Pain Management Following Dental Extractions (DIODE): Protocol for a Cluster Randomized Trial

Abstract: Background Overdose deaths from prescription opioid analgesics are a continuing crisis in the United States. Opioid analgesics are among the most frequently prescribed drugs by dentists. An estimated 5 million people undergo third-molar extractions in the United States each year, resulting in postoperative pain. Studies show that, in most cases, the combination of ibuprofen and acetaminophen is an effective alternative to commonly prescribed opioid analgesics for the management of postextraction pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Figure 1 depicts the study flow. The study protocol and methodological details have been previously reported [ 19 ]. The HealthPartners Institutional Review Board approved the study.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1 depicts the study flow. The study protocol and methodological details have been previously reported [ 19 ]. The HealthPartners Institutional Review Board approved the study.…”
Section: Methodsmentioning
confidence: 99%
“…The patient education was either automatically printed when a patient checked in for a scheduled extraction or was printed by the dentist at the point of care. Further details about the trial are described elsewhere (17). The survey results presented here are an exploratory analysis in the context of this larger project.…”
Section: Methods Interventionmentioning
confidence: 99%
“…The study was conducted in the HealthPartners Dental Group, which is embedded within a healthcare system. Further information about the design and conduct of the study is published elsewhere 10 …”
Section: Objectivesmentioning
confidence: 99%
“…7,8 Despite the widespread use of opioids in dentistry, evidence shows that adequate pain relief following dental extractions can usually be achieved with non-opioid analgesics. 9 A well-designed clinical decision support (CDS) system 10,11 can support dentists in providing optimal care by pulling in relevant medical conditions and medications so the prescribing decision does not create needless side effects or drug interactions. This includes safer, evidence-based pain management for patients and not resorting to opioids when a safer alternative would provide effective pain management.…”
Section: Introductionmentioning
confidence: 99%